Genetic architecture of yield traits and oil content in Indian mustard (Brassica juncea) - CHAUDHARY, MOHIT; AVTAR, RAM; SINGH, VIVEK K; ANU, ANU; MAHAVIR, MAHAVIR (The Indian Journal of Agricultural Sciences, 2021)
The generation mean analysis was carried out to estimate nature and magnitude of gene effect for yield traits and oil content in two crosses RH 0749 × RLC-3 and RH 0749 × PDZ-1 of Indian mustard [Brassica juncea (L.) Czern & Coss]. Significance of scaling test as well as χ2 in joint scaling test showed the presence of digenic or higher order interactions for all characters except for days to maturity in cross RH 0749 × RLC-3. Additive gene effects (d) were important for days to maturity, number of secondary branches per plant, number of seeds per siliqua, 1000-seed weight and seed yield per plant. Both additive (d) and dominance (h) gene effect were important for plant height, number of primary branches per plant, main shoot length, number of siliquae on main shoot, siliqua length and oil content. The dominant × dominant (l) type of gene interaction and duplicate epistasis was observed for most of the character in two crosses except for seed yield per plant in cross RH0749 × PDZ-1 for which complementary epistasis was observed. These results suggested that substantial improvement in yield may be achieved through recurrent selection and heterosis breeding.